A Meta‐Analysis of Single‐Case Research on Mathematics Word Problem‐Solving Interventions for English Learners with Learning Disabilities and Mathematics Difficulties. Issue 4 (9th October 2020) - Lei, Qingli; Mason, Rose A.; Xin, Yan Ping; Davis, John L.; David, Marie; Lory, Catharine
Abstract: This single‐case meta‐analysis is the first to provide a quantitative synthesis of the published literature on mathematics word problem‐solving intervention studies for English learners with learning disabilities and mathematics difficulties. A total of ten single‐subject studies were included for analysis. The current study investigated the magnitude of the effect of mathematics interventions targeting the improvement of students' mathematics word problem‐solving performance, and analyzed variables that moderated this effect. Results indicate a moderate overall effect size of 0.81 (95% CI [0.71, 0.90]) on word problem‐solving performance for English learners with learning disabilities and mathematics difficulties. Moderator variables such as the implementer of the interventions, instructional focus, and word problem‐solving content significantly moderated the mathematics intervention effects.